High-Frequency Chest Wall Oscillation versus Conventional Airway Clearance Techniques in Non-Cystic Fibrosis Bronchiectasis: A Meta-Analysis - Dzaki Murtadho; Irvan Medison; Deddy Herman (HM Publisher, 2025)
Background: Non-cystic fibrosis bronchiectasis (NCFB) is a chronic lung disease characterized by irreversible airway dilation and impaired mucociliary clearance, leading to chronic cough, sputum production, and recurrent infections. This meta-analysis aims to compare the efficacy of high-frequency chest wall oscillation (HFCWO) with conventional airway clearance techniques (CACT) in adults with NCFB. Methods: A systematic search of PubMed, Embase, Cochrane Library, Web of Science, and Scopus databases was conducted from January 2013 to March 2024. Randomized controlled trials (RCTs) comparing HFCWO with CACT (postural drainage, percussion, active cycle of breathing technique, positive expiratory pressure therapy) in adults with NCFB were included. The primary outcomes were a change in forced expiratory volume in one second (FEV1) and sputum weight. Secondary outcomes included quality of life, exacerbation frequency, and adverse events. The risk of bias was assessed using the Cochrane Risk of Bias 2 tool. Data were pooled using a random-effects model, and heterogeneity was assessed using the I² statistic. Results: Nine RCTs involving a total of 485 participants were included. The meta-analysis showed no statistically significant difference in FEV1 change between HFCWO and CACT (mean difference [MD] 0.05 L, 95% confidence interval [CI] -0.02 to 0.12; I² = 45%). HFCWO was associated with a statistically significant increase in sputum weight compared to CACT. SGRQ total score showed a statistically significant improvement in the HFCWO group compared to CACT (MD -4.21, 95% CI -7.88 to -0.54; I² = 58%). Conclusion: HFCWO may provide a modest benefit in terms of increased sputum clearance and improved quality of life compared to CACT in adults with NCFB. However, there was no significant difference in lung function (FEV1) or exacerbation frequency. The moderate to high heterogeneity in some outcomes suggests that further research is needed to confirm these findings and identify patient subgroups who may benefit most from HFCWO.